2016
DOI: 10.1007/s12028-016-0252-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Venous Thromboembolism in Patients with Large Hemispheric Infarction Undergoing Decompressive Hemicraniectomy

Abstract: The rate of DVT and PE is remarkably high in patients with large hemispheric infarction undergoing decompressive hemicraniectomy despite prophylactic measures. We recommend routine screening for DVT in this population. Interventions beyond the standard prophylactic measures may be necessary in this high-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…9,10,37 By contrast, DVT rates exceeding 30% have been reported with routine screening Doppler ultrasonography after moderate-to-severe traumatic brain injury (without chemoprophylaxis) 13 or large hemispheric infarction requiring decompressive hemicraniectomy (with chemoprophylaxis). 38 We found no association between VTE and age, gender, or any particular diagnostic group. Compared to the previous studies of medical–surgical critically ill patients reporting VTE rates of 2% to 10%, 2 –5 the frequency of VTE in neurocritical care patients appears to be on the lower side; a higher incidence of VTE in sepsis and septic shock patients might explain this finding.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…9,10,37 By contrast, DVT rates exceeding 30% have been reported with routine screening Doppler ultrasonography after moderate-to-severe traumatic brain injury (without chemoprophylaxis) 13 or large hemispheric infarction requiring decompressive hemicraniectomy (with chemoprophylaxis). 38 We found no association between VTE and age, gender, or any particular diagnostic group. Compared to the previous studies of medical–surgical critically ill patients reporting VTE rates of 2% to 10%, 2 –5 the frequency of VTE in neurocritical care patients appears to be on the lower side; a higher incidence of VTE in sepsis and septic shock patients might explain this finding.…”
Section: Discussioncontrasting
confidence: 54%
“…57 High BMI has been reported to be an independent risk factor for thromboprophylaxis failure in critically ill patients and has been associated with VTE in patients with subarachnoid hemorrhage and large hemispheric infarction undergoing decompressive hemicraniectomy in previous studies. 5,9,38,39,58 Higher weight-based doses of anticoagulant prophylaxis have been reported to maintain peak plasma anti-Xa levels within or near the recommended range for thromboprophylaxis and to reduce in-hospital VTE in morbidly obese patients without increasing the risk of bleeding. [59][60][61][62] Further study is required to determine the efficacy and safety of weight-based chemoprophylaxis in obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have focused on one single medical complication and its management in DHC cohorts, with little discussion of neurological complications. [23][24][25][26][27] Moreover, there are few data available to indicate the impact of different stroke-related complications on unfavorable outcome in patients with LHI. In our cohort, we found that LHI patients with unfavorable outcomes had more frequent stroke-related complications than those with favorable outcomes.…”
Section: Discussionmentioning
confidence: 99%